Jeersanidhi Award Lecture - The four major species of root-knot nematodes - Current status and management approach - KHAN, M. WAJID (Indian Phytopathology, 2002)
A review of Meloidogyne incognita, M. javanica, M. arenaria and M. hapla, and their host races in India is given. A discussion of the current management approaches is also included.